Benzodiazepine receptor increases after repeated seizures: evidence for localization to dentate granule cells. - Valdes, F (1982)
Repeated seizures, whether induced by kindling or electroshock, result in increased numbers of benzodiazepine receptors in hippocampal formation membranes. We sought to determine the cellular constituents containing the receptor increases. Binding studies of microdissected samples localized the receptor increases to fascia dentata. [3H]Flunitrazepam autoradiographic studies showed increases of silver grain density over the granule cell and molecular layers of fascia dentata but not in other regions of hippocampal formation. Destruction of granule cells by colchicine or neonatal x-irradiation was associated with marked decrease of benzodiazepine receptor binding. Together, these results provide evidence for localization of the receptor increases to the somata and dendritic tree of the granule cells. We suggest that this cellular localization may provide a clue to the network of altered neural circuitry underlying amygdala kindling.